2019
DOI: 10.1111/1744-7917.12661
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behavior, life history, and virus transmission ability of Bemisia tabaci Mediterranean species (Hemiptera: Aleyrodidae) under elevated CO2

Abstract: The continuous rise of CO 2 concentrations in the atmosphere is reducing plant nutritional quality for herbivores and indirectly affects their performance. The whitefly (Bemisia tabaci, Gennadius) is a major worldwide pest of agricultural crops causing significant yield losses. This study investigated the plant-mediated indirect effects of elevated CO 2 on the feeding behavior and life history of B. tabaci Mediterranean species. Eggplants were grown under elevated and ambient CO 2 concentrations for 3 weeks af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…In recent years, there have been some reports on the effects of other abiotic factors, namely CO 2 , O 3 , and water stress, on the spread of viral diseases as a consequence of the extreme environmental changes [48,[51][52][53][54][55][56][57][58]. Dader and colleagues [53] thoroughly examined the impact of elevated CO 2 levels (eCO 2 ) on M. persicae life history, feeding behaviour, and the virus transmission ability of Cucumber mosaic virus (CMV; cucumovirus) to pepper plants (Capsicum annuum), transmitted in a non-circulative manner.…”
Section: Impact Of Abiotic Stresses On Viral Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there have been some reports on the effects of other abiotic factors, namely CO 2 , O 3 , and water stress, on the spread of viral diseases as a consequence of the extreme environmental changes [48,[51][52][53][54][55][56][57][58]. Dader and colleagues [53] thoroughly examined the impact of elevated CO 2 levels (eCO 2 ) on M. persicae life history, feeding behaviour, and the virus transmission ability of Cucumber mosaic virus (CMV; cucumovirus) to pepper plants (Capsicum annuum), transmitted in a non-circulative manner.…”
Section: Impact Of Abiotic Stresses On Viral Transmissionmentioning
confidence: 99%
“…In particular, as evoked in the previous section, abiotic stresses may affect the feeding behaviour and fitness of sap-sucking insects through changes in plant physiology, alteration of host plant quality (i.e., secondary metabolites, essential amino acids, carbohydrates pools, etc. ), and activation of plant defences [67][68][69], with potential consequences for virus transmission efficiency [53,54,56]. Some aphid species are reported to have a greater reproductive capacity under drought conditions than under non-drought conditions [70].…”
Section: Vector Feeding Behaviour Under Abiotic Stressesmentioning
confidence: 99%
“…genetically modified with the Bt gene and grown in the presence of eCO 2 . Furthermore, Coviella, Morgan, and Trumble (2000) However, it should be noted that previous investigations have shown that a decrease in the nitrogen content and an increase in the C:N ratio are not directly linked to the Bt protein (Jablonski, Wang, & Curtis, 2002;Peñalver-Cruz et al, 2019;Sun, Su, & Ge, 2010;Yifei et al, 2018). In addition, we observed morphological changes in the soybean plants grown in the presence of eCO 2 .…”
Section: Discussionmentioning
confidence: 52%
“…aphids and whiteflies), alterations in the metabolic pathways and plant nutritional quality can influence their feeding behaviour, biology and ability to transmit plant pathogens, which may differ depending on a specific host plant (Coviella & Trumble, 1999; Dáder, Fereres, Moreno, & Trębicki, 2016; Jones, 2016; Robinson, Ryan, & Newman, 2012; Trębicki et al., 2017; Zavala, Gog, & Giacometti, 2017). It has been shown that plants grown under elevated CO 2 favour population abundance, feeding efficiency and fitness of certain aphid (Guo et al., 2017; Xie et al., 2014) and whitefly species (Li, Liu, Xiao, Li, & Chen, 2011; Peñalver‐Cruz et al., 2019); other studies have demonstrated that other aphid species, such as Aulacorthum solani (Hughes & Bazzaz, 2001), and whiteflies (MEAM1) (Wang, Wang, Sun, & Ge, 2014) did not manifest any physiological or populational adverse effects under eCO 2 . Conversely, eCO 2 may negatively influence physiological (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the less efficient ToCV primary virus spread shown in the B. tabaci-resistant tomato genotype could have been the result of a restricted B. tabaci interaction with these plants owing to their reduced attractiveness to the insect landing (Rodríguez-López et al, 2011). However, the relevance of B. tabaci feeding behavior after landing on a plant and the possible effects on virus transmission has also been discussed (Peñalver-Cruz et al, 2020). ToCV is a phloem-restricted virus in tomato and its inoculation is mainly associated with effective stylet activities in phloem sieve elements (Prado Maluta et al, 2017).…”
Section: Discussionmentioning
confidence: 99%